Implementasi manajemen pembelajaran daring pada masa pandemi covid-19 di sekolah dasar - Kusneini, Nur; Marmoah, Sri; Hadiyah, Hadiyah (Didaktika Dwija Indria, 2022)
This research aims to describe online learning planning, implementation of online learning, and evaluation of online learning. The method used in this research is qualitative method. The data in this study were the results of interviews with homeroom teachers of grades I-VI at SD Negeri Sumber IV Surakarta, observations of the learning process, and documentation studies. Data collection techniques using interviews, observation, and documentation. The data analysis technique in this study is interactive analysis with the stages of data collection, data reduction, data presentation, and drawing conclusions. Triangulation technique using data sources. The results of this study are that learning management at SD Negeri Sumber IV includes learning planning with the result that learning planning at the school is preparing learning tools including annual programs, semester programs, syllabus, and learning implementation plans, but the lesson plans are still incomplete in the activities section. learning. Teaching materials are also prepared such as textbooks and learning videos from YouTube, learning media using WhatsApp Group, Google Classroom,  Google Meet, and Zoom.